LEGAL HARMONIZATION IN ASEAN ECONOMIC COMMUNITIES (LOOKING FOR THE BEST LEGAL HARMONIZATION MODEL) - Candra Irawan (Universitas Bengkulu, 2018)
ASEAN countries need to be encouraged to make responsive, effective, efficient, non-discriminatory, and pro-competition regulations that are adjusted AEC Blueprint 2025. This means that each ASEAN country needs to harmonize regulations so that the rules that apply in each national territory do not conflict with each other and in line with AEC Blueprint 2025. There is no clear regulation system in force in ASEAN, nor is the legal harmonization mechanism and binding power of the AEC. Questions that should be asked, is the legal basis for the implementation of AEC Blueprint 2025 deliberately based on international agreements only (intergovernmental, soft law) and not upgraded to legal force (primacy principles, hard law)? The most important thing is that there is a shared awareness to build the ASEAN region's economy more productive, advanced and shared prosperity. The commitment is not enough just to use soft law approach, but must be followed by hard law approach (primacy principles). ASEAN leaders should hold talks and seek agreement to implement the principle of supranational (primacy principles) that the implementation of the AEC Blueprint 2025 be adhered to by all member states.